Roberto Freire: tesão e anarquia - Simões, Gustavo Ferreira (2011)
The emergence of the author function in the 19th century, as pointed out by Michel Foucault, was characterized by the investment in organizing, affiliating and homogenizing the diffusion of discourses from previous centuries. The author signature has risen as an existence entitled with a different status from those that used the word ordinarily at the same time that it was identified as the possible danger to be fought. Considering Foucault s suggestions, I have followed Roberto Freire s writings, with no intent of explaining it, while articulating it with his life experiences since the liberation of DOPS s dungeons, in 1965, a year after the military coup of 1964, until the publication of his last writings in the end of the 20th century. Freire s writings update the exercise of social literature undertaken by some libertarians in the beginning of the 20th century in Brazil. However, his books are not inspired by the thought of the socalled classical anarchists, but by the practices that have emerged with the protests, particularly those connected to customs, triggered by the events of 1968. Freire, dissociating himself from the projects of revolution, began to value, in the 1970s, through his books and life, certain experiences with the body, in the present, associating it to an anarchist sensualization of the existence. The analysis of his journey since 1960 when he was an activist in Ação Popular and through his experiences with The Living Theater, Wilhem Reich and the anarchism in the 1980 and 1990 was possible given the distance he kept from the notion of author. Freire s writings have been developed in movement. Therefore, one cannot impose on it a unity or explanatory restrain. Freire has dangerously sailed with his literature in the late 20th century. The navigation, according to Michel Foucault, was a privileged metaphor to those immersed in an ethical and aesthetical life in the Hellenistic and Roman antiquity. By affirming this navigation, this existence, he moved like a libertarian pilot, like an anarchist pirate